Mortality trends in extremely premature neonates: insights from the CDC WONDER database from 1999 to 2023 - Hammond, Rebecca; Phan, Martin; Foley, Olivia; Tauseef, Abubakar (Frontiers in Pediatrics, 2025)
IntroductionPremature birth is associated with significant morbidity and mortality. Risk increases with younger gestational age. The ICD-10-CM code classifies extremely immature neonates as being born at less than 28 weeks gestation. Antenatal and neonatal interventions have improved outcomes overall. This study evaluates trends in extreme prematurity related mortality to determine if outcomes are evenly distributed among demographic groups, including pre and post COVID data.MethodsThe CDC WONDER database was utilized to gather data on extreme immaturity related mortality in infants <1 year old from 1999 to 2023. Joinpoint regression was subsequently utilized for data analysis, analyzing crude mortality rate (CMR), annual percent change (APC), and average annual percent change (AAPC), stratifying data by sex, race, region, and urban vs. rural locality.ResultsExtreme immaturity resulted in 92,917 deaths among neonates in their first year of life from 1999 to 2023. Overall CMR significantly decreased across the study period [AAPC −1.14* 95% CI (−1.45, −0.83)], with both female and male neonates experiencing a significant decrease in CMR [AAPC −1.32* 95% CI [−1.63, −1.06] and AAPC −1.10* 95% CI [−1.57, −0.68] respectively]. Black or African American neonates had a higher CMR than all other racial and ethnic groups. Of all the racial and ethnic groups, CMR significantly decreased only for Black or African American and White neonates [AAPC −1.98* 95% CI [−2.62, −1.46] and AAPC −1.12* 95% CI [−1.42, −0.82] respectively]. All US regions experienced significant declines in CMR except for the West [AAPC −0.72 95% CI (−1.32, 0.19)]. CMR decreased in urban localities but did not decrease in rural localities [AAPC −0.93* 95% CI [−1.24, −0.59] vs. AAPC 0.12 95% CI [−0.51, 0.96]].ConclusionsWhile medical advancements have improved outcomes for neonates born extremely premature, these outcomes are not evenly distributed amongst demographic groups in the United States. There was no large change in trends associated with the COVID-19 pandemic.